Detection, Identification, Clinical and Histopathological Features of Novel Ostrich Parvovirus in Iran - Majidi, Sanaz; Araghi, Mostafa; Nazem Shirazi, Mohammad Hosein; Pourbakhsh , Seyed Ali; Charkhkar, Saied; Dezfoulian, Omid; Danaeifard, Mohammadreza; Razmyar, Jamshid (Journal of Poultry Sciences and Avian Diseases, 2025)
Recently, a novel disease affecting ostriches has emerged in several regions of Iran. This disease is characterized by sudden death, diarrhea, and paralysis. This outbreak has significantly impacted the Iranian ostrich farming industry, leading to substantial economic losses. This study aims to characterize and identify a novel ostrich parvovirus (OsPV) originating from chicks that exhibited paralysis and diarrhea in ostrich flocks across three provinces in Iran. Samples were collected from paralyzed ostriches and evaluated through clinical examination, histopathology, molecular techniques, and phylogenetic analysis. Before necropsy, radiographs were taken to assess for trauma. Affected tissues were evaluated histopathologically. PCR was performed to amplify the NSP-VP1 gene, and two positive samples, named SANA/OsPV/001/Ostrich/IR/2024 and SANA/OsPV/002/Ostrich/IR/2024, were sent for sequencing using both forward and reverse primers. A comprehensive analysis of the NSP-VP1 gene of OsPV was conducted to elucidate its genetic characteristics. Throughout 2024, four distinct isolates of OsPV were detected in three provinces: Tehran, Razavi Khorasan, and Isfahan. A 90 bp fragment of the NSP-VP1 gene of OsPV was detected in multiple organs, indicating that the new OsPV variant has multiple organ tropism. Radiographic findings revealed severe enteropathy and maldigestion/absorption alongside cloacal distention. Histopathological analysis showed metaplastic changes in the sciatic nerve, extensive necrosis of the intestinal mucosa, acute tubular necrosis, glomerulonephritis in the kidneys, and signs of pneumonia. Comparative sequence analysis of the NSP-VP1 gene revealed a high degree of homology between the SANA/ OsPV / 001/ Ostrich/ IR/ 2024 isolate and strains from Turkey, the United Kingdom, and Russia. Notably, the SANA/OsPV isolates were found to be closely related to goose parvovirus and other ostrich parvovirus strains. This study represents the first documented molecular detection and characterization and a histopathological assessment of ostrich parvovirus in Iran. Our findings contribute to a better understanding of the virus’s epidemiology and impact on the ostrich farming sector, underscoring the need for ongoing surveillance and control measures in affected regions.